Належний суб’єкт збирання як гарантія допустимості доказів - Чернега, Ірина Леонідівна; Чернега, Ирина Леонидовна; Chernega, Irina (Одеса : Юрид. л-ра, 2014)
The article is devoted to subjects of criminal proceedings, which are entitled to collect proofs, the features of their activities that effect on the admissibility of collected proofs and the research of changes in the Institute in accordance with the new legislation.
Чернега І. Л. Належний суб’єкт збирання як гарантія допустимості доказів / І. Л. Чернега // Актуальні проблеми держави і права : зб. наук. пр. / редкол.: С. В. Ківалов (голов. ред.), В. М. Дрьомін (заст. голов. ред.) Ю. П. Аленін [та ін.] ; МОН України; НУ ОЮА. – Одеса : Юрид. л-ра, 2014. – Вип. 74. – С. 402-406.
Keywords: докази; допустимість доказів; властивості доказів; суб’єкти кримінального процесу; належний суб’єкт; доказательства; допустимость доказательств; свойства доказательств; субъекты уголовного процесса; надлежащий субъект; proofs; admissibility of proofs; properties of proofs; subjects of criminal proceedings; proper subject